Immediate dentin sealing: effect of sandblasting on the layer thickness - Kovalský, Tomáš; Voborná, Iva; Ingr, T; Morozova, Yulia; Míšová, Eva; Hepová, Monika (Bratislavské lekárske listy, 2022)
OBJECTIVES: The objective of this study was to observe and to measure the impact of corundum sandblasting on the thickness of the Immediate dentin sealing layer. METHODS: 20 recently extracted molars were collected and divided randomly into two groups. A standardized preparation was performed on each tooth and the Optibond FL dentin bonding agent (Kerr, Orange, USA) was applied on the prepared surface according to the manufacturer’s instructions. The surface was then partially sandblasted. RONDOflex plus 360 (KaVo, Bieberach an der Riss, Germany) and Airsonic Mini-Sandblaster (Hager et Werken, Duisburg, Germany) were used. Microscope observations were made. RESULTS: The arithmetic mean of the Optibond FL dentin bonding agent film thickness was 48.72 μm (Group 1=45.55 μm and Group 2=51.88 μm). The dentin bonding agent layer thickness was reduced to the average value of 17,12 μm by RONDOflex plus 360 sandblasting (Group 1). The zero value was recorded in 16 % of the locations. The Airsonic Mini-Sandblaster sandblasting changed the average thickness of the dentin bonding agent layer to 13.25 μm with 31 % of zero values (Group 2). CONCLUSION: The results of this research lead to a reflection on modifications of the immediate dentin sealing procedure (Tab. 4, Fig. 3, Ref. 28).
Keywords: moláry; Statistics as Topic; zubní sklovina; lidé; Air Abrasion, Dental; Dentin-Bonding Agents; Dental Enamel; mikroskopie; Aluminum Oxide; statistika jako téma; dentinová adheziva; Molar; Microscopy; oxid hlinitý; pískování zubů; Humans